Economic development : its conditions and strategies - Ikoku, S. G. (Ile Ife, Nigeria : University of Ife Press Published [for] the Faculty of Arts, 1974)
This book is a series by the University of Ife which examines the economic development its conditions and strategies.
Includes bibliographical references: p. 16- 17.
ahz 04/04/2019
Loans
Keywords: Economic development; Nigeria